PENGARUH PEMBERIAN KOMPENSASI FINANSIAL TERHADAP DISIPLIN KERJA GURU TAMAN KANAK-KANAK SE-KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Desi Ratnasari Desi Ratnasari; Wilson Wilson '; Yeni Solfiah Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Desi Ratnasari. The effect of financial compensation for teachers working discipline Kindergarten District of Rambah Hilir Rokan Hulu Regency. The purpose of this study was to determine whether there is any effect of financial compensation for teachers working discipline Kindergarten District of Rambah Hilir Rokan Hulu Regency. This type of research is a correlation study, this research variable consists of two variables: financial compensation variable and variable work discipline. The study population is that all teachers Kindergarten District of Rambah Hilir Rokan Hulu Regency as many as 40 people. Based on the results of studies using Chi Square test analysis was not a significant difference between the provision of financial compensation to the working discipline Kindergarten teacher District of Rambah Hilir Rokan Hulu Regency. It can be seen from the acquisition value obtained by calculating the value of X2 table = 16.919 with α = 5% and X2 count = 2.130. Because X2 count <X2 tables or 2,130 <16.919 thus null hypothesis (Ho) is received. It means there is no financial compensation for the effect of labor discipline Kindergarten teachers throughout the District of Rambah Hilir Rokan Hulu Regency.Keywords: Financial Compensation, Work Discipline